Cytokeratin7 expression in gastric and colorectal adenocarcinoma: Correlation with prognostic factors - Mohammadreza Jalalinadoushan; Sepideh Siadati; Ali Davati; Gholamreza Torabi-Parizi; Samira Ghasemi (Babol University of Medical Sciences, 2015)
Background: Gastric and colorectal adenocarcinoma are the second and the fifth most common cancers in Iran, respectively. Expression of cytokeratin 7 (CK7) is established in most malignancies including gastric and colorectal adenocarcinoma. Demonstration of Ck7 could be related to prognostic factors and help to the better management of the patients. The objective of our study was to evaluate the CK7 expression in gastric and colorectal adenocarcinoma and its correlation with other prognostic factors.  Methods: This cross-sectional study was performed on 99 tissue blocks from patients with gastric or colorectal adenocarcinoma undergoing surgery. Tumor grade, tumor size, depth of invasion and metastasis to lymph nodes were determined. Then, the expression of CK7 was studied using immunohistochemistry staining.  Results: Expression of CK7 was 50% and 33.8% in gastric and colorectal adenocarcinoma, respectively. There was not only a significant correlation between CK7 expression and tumor size (r=0.267, P=0.009) but also histologic grade (r=0.222, P=0.028).  Conclusion: CK7 could be more expressed with the increase in tumor size and was associated with poorly differentiated gastric and colorectal adenocarcinoma. However, with these results gathered, it is highly recommended that further studies will be conducted to reveal the exact prognostic role of this factor.